Case report: Occult lymph nodal metastasis in sub-centimeter lung cancer: a report of seven cases and review of literature - Wang, Xiao; Li, Yingxin; Shi, Xiaoxuan; Liu, Zhengcheng (Frontiers in Oncology, 2025)
BackgroundOccult lymph node metastasis (OLNM) after surgery for stage IA sub-centimeter lung cancer is an extremely rare clinical situation, with few reported cases in the literature. Further investigation is warranted into the clinical characteristics of patients and the radiological features of lung nodules. Here, we aim to provide a comprehensive insight into this tumor type.MethodsWe present cases that sub-centimeter non-small cell lung cancer (NSCLC) patients who underwent surgery at our center and were found to have OLNM in postoperative pathology. This is the first time such cases have been reported. We reviewed the existing literature on this rare event and collected detailed clinical, histopathological, and radiological data for analysis.ResultsA total of 7 sub-centimeter lung cancer patients were diagnosed with OLNM based on routine pathology, including 1 male and 6 females, with an average age of 58.7 ± 9.3 years. All patients had no clinical symptoms and were found by physical examination, with follow-up durations ranging from 1 week to 3 years. Among these patients, 4 exhibited mediastinal lymph node metastasis. Preoperative chest CT in all patients showed pure-solid nodules (PSN), and 6 patients changed the surgical procedure based on intraoperative frozen sections results. Routine pathology revealed that all adenocarcinoma patients presented high-risk factors for recurrence, including visceral pleural invasion (VPI), spread through air spaces (STAS), vascular invasion, and poorly differentiated tumor.ConclusionSub-centimeter lung cancers with radiological feature of PSN are at risk for lymph node metastasis. Surgeons should pay close attention to intraoperative rapid pathology results to prevent inadequate surgical treatment. Adenocarcinoma patients often present with one or more high-risk factors for recurrence, active adjuvant treatment and follow-up are necessary.